Zginanie Mikropolarnej Belki Wspornikowej Obciążonej Momentami - Ieşan, D. (Engineering Transactions, 1971)
The considerations presented in the paper concern the problem of bending of homogeneous and isotropic beams by terminal couples on the basis of the linear theory of micropolar elasticity. The model of the micropolar body is due to A. C. Eringen.